The Use of Miming Game for English Vocabulary Acquisition at an Islamic Junior High School - Ulayra Nurul Hazizah, Ulayra Nurul Hazizah; Mujad Didien Afandi; Nailul Authar; Djuwari; Rizqi Febrian Pramudita; Meiga Rahmanita (Universitas Nahdatul Ulama Surabaya, 2024)
The inspiration for this study is to use various teaching techniques in acquiring English vocabulary to avoid monotonous activities that make students bored and not interested in learning. Teachers can use miming games as a teaching technique to make the learning process in the classroom more fun and easier to understand. Miming games also allow students to acquire vocabulary to easily remember and understand a word. The focus of this research is 1) the use of miming game to acquire English vocabulary, and 2) student responses about the use of miming game to acquire English vocabulary. This study used qualitative methods, with data collection techniques used such as observation, questionnaires, interviews, and documentation. The data was analyzed and then triangulated for the inferences. The results of this study shows that, as based on the observations in the field notes, the students enjoyed the learning process and easily memorized the new vocabulary. In addition, they also felt interested, happy, enjoyable, and the learning process was efficient for acquiring the vocabulary by miming game.